The moderating effect of gender on physical activity participation and physical fitness in children - Howard Gomwe; Lesego Phiri; Chioneso Show Marange (AOSIS, 2024)
Background: The level, direction or presence of the relationship between perceived physical activity (PA) participation and physical fitness (PF) in children may differ by gender and this will assist in designing gender-specific interventions to promote PA participation, which in turn improves PF levels. Aim: This study aimed to establish the moderating effect of gender on the relationship between perceived PA participation and PF. Method: A cross-sectional study was conducted with a cohort of 870 primary school children aged 9-14 years old. Perceived PA participation was measured using the PAQ-C questionnaire while PF levels were measured using cardiorespiratory endurance (i.e. VO2 max). Results: The results showed significant gender differences for perceived PA participation levels (t = −3.40, p ≤ 0.001) and PF (t = −11.59, p ≤ 0.001), with boys reporting higher levels than the girls. Perceived PA participation had a positive, weak and statistically significant correlation with PF (r = 0.251; p ≤ 0.001). Gender significantly moderates the relationship between perceived PA participation and PF (β3 = 3.518; 95% confidence interval [CI]: 0.642 to 6.395; p = 0.017). Conclusion: The moderating effect of gender on the relationship between perceived PA participation and PF highlights the differences in physiology as well as the societal PA associated roles played by boys and girls. Contribution: The study has established that the relationship between perceived PA participation and PF is more pronounced among boys than girls.